Effect of Gamma irradiation on The Optical properties of (PVA: CuCl2) films - Salman , Seham Hassan; Abbas , Esraa Akram; abd, Enas Yasseen; Abbas , Shaimaa Akram (Iraqi Journal of Science, 2022)
The study effect irradiation on optical properties of film (PVA: CuCL2) prepared by casting method, with thickness of (30±1) μm. And used Cs137 to obtained Gamma ray with energy (662)keV and time irradiation(5,6 and 7) weeks and affectivity (4.3) ci. The spectra absorbance and transmittance register in range (300-1100) nm .Results show that the optical band gap for (PVA: CuCl2) decreasing after irradiation with gamma ray from (3.2,3.1,3 and 2.7)eV, urbach energy values increase with the increasing time radiation. And the absorption constants (α,k,n,) and the optical conductivity are changing after irradiated with gamma ray .